Boron nitride modified PAN ultrafiltration membranes with im-proved water permeance and dye rejection performance - Ye Zhao; Lei Chen; Yuan Zuo; Baiyan Zhu; Xueli Liu; Yujin Jia (Desalination and Water Treatment)
Polyacrylonitrile (PAN) has attracted obvious attention from research professionals due to its chemical and thermal stability. To further enhance the PAN membrane performance, it becomes crucial to optimize the film forming conditions. This study aims to determine whether hexagonal boron nitride (h-BN) can be used to boost the PAN ultrafiltration (UF) membranes performance. The nonsolvent induced phase inversion process (NIPS) approach was employed to manufacture PAN nanocomposite ultrafiltration membranes. The prepared PAN membranes with different h-BN loadings were characterized via morphological, wetting, water transport properties and so on. Based on the hydrophilicity test results, the optimized B-0.8 membrane had a water contact angle of 42°, suggesting its good hydrophilicity. The B-0.8 UF membrane exhibited improved water permeability (from 174.5 to 234.4 L m−2 h−1 bar−1), enhancing the removal capacity of dyes (from 68.7 % to 99.3 % for CR and from 94.1 % to 99.3 % for CB-G-250), and a remarkable 99.0 % BSA rejection. Moreover, these characteristics render the PAN nanocomposite UF membrane with considerable potential for the decontamination of dye wastewater.